Matthew Buckingham, Abraham Cruzvillegas, Mark Dion, Teresita Fernández, Trevor Paglen, Rayyane Tabet, Diana Thater on Robert Smithson - Buckingham, Matthew 1963-; Cruzvillegas, Abraham 1968-; Dion, Mark 1961-; Fernández, Teresita 1968-; Paglen, Trevor 1974-; Tabet, Rayyane 1983-; Thater, Diana 1962- (Dia Art Foundation, 2020)
This is the fifth volume in a series that builds upon Dia Art Foundation's 'Artists on Artists' lectures. The contributors to 'Artists on Robert Smithson' engage with Smithson's work in myriad ways: Matthew Buckingham's essay highlights Smithson's preoccupation with the ways that histories of the earth are constructed and contested; Abraham Cruzvillegas considers Smithson's work with broken glass and architecture; Mark Dion's didactic approach to the life and work of the artist recounts the conceptual and evolutionary conditions that led to his birth and development; Teresita Fernández confronts the limitations of dominant histories of place, art and the monumental; Trevor Paglen considers Smithson's iconic spiral and his fascination with natural history; Rayyane Tabet weaves together a history of basalt that reveals themes of colonialism, surveillance and strife; and finally, engaging with the science fiction canon and its cinematic conventions, Diana Thater provides a close reading of Smithson's Spiral Jetty film
Keywords: Smithson, Robert -- 1938-1973; Smithson, Robert / Criticism and interpretation; Smithson, Robert; Criticism, interpretation, etc; Aufsatzsammlung